Indicators for agroecological transition: Food security, nutrition, well-being, promotion of a sustainable food model (2023)
Agroecology is a viable alternative confronting the impressive model of industrial agriculture. To project the concept of Agroecology beyond theoretical definitions to practical and quantifiable principles, it is necessary to have analysis, communication and evaluation tools that support and allow the evaluation of positions. Indicators are quantifiable tools that make the obtention of numerical variables possible to compare the different models. This study aims to establish a proposal of quantifiable indicators to evaluate the direct impact of aspects related to food and nutritional quality, responding to the demand for an integrated evaluation of agroecological systems, thus improving the tools for calculating current indicators. The proposed parameters cover aspects that have a greater or lesser impact on the daily diet, such as the variability of the foods that make up the dish, their contribution to food safety, the nutritional composition and bioactive components, organoleptic aspects, degree of processing and transformation of the food consumed, environmental aspects that influence the production model and their influence on human well-being. As well as parameters of the social sphere, such as the impact on the economy of scale, on attributes of proximity, temporality, as well as indicators related to social justice. The proposal can help to obtain assessment before or after the implementation of agricultural policies towards the agroecological transition, allowing self-assessment, and provide verifiable data after a change in agricultural policies when redesigning or introducing agroecological strategies.